Selection bias in clinical studies of first-episode psychosis: A follow-up study - Walta Maija; Laurikainen Heikki; Armio Reetta-Liina; From Tiina; Tolvanen Arvi; Salokangas Raimo KR; Hietala Jarmo (ELSEVIER, 2022)
Objectives: Selection bias is a concern in studies on psychotic disorders due to high dropout rates and many eligibility criteria for inclusion. We studied how representative the first-episode psychosis study sample in the Turku Early Psychosis Study (TEPS) was.
Methods: We screened 3772 consecutive admissions to the clinical psychiatric services of Turku Psychiatry, Finland, between October 2011 and June 2016. A total of 193 subjects had first-episode psychosis and were suitable for TEPS. Out of 193 subjects, 101 participated (PA) and 92 did not participate (NPA) in TEPS due to refusal or contact problems. We retrospectively used patient register data to study whether NPA and PA groups differed in terms of clinical outcomes during 1-year follow-up.
Results: In overall sample, the NPA group had a significantly higher rate of discontinuation of clinical treatment than the PA group (48.9 % vs 29.7 %, p = 0.01). In the hospital-treated subsample chi-square tests did not indicate statistically significant differences between the NPA and PA groups in the rate of involuntary care (69.7 % vs 62.7 %, p = 0.34), coercive measures (36.0 % vs 22.7 %, p = 0.06), and readmissions during the follow-up (41.5 % vs 33.8 %, p = 0.31), respectively.
Conclusion: The differences in clinical outcomes and treatment characteristics in the non-participating and participating groups were relatively modest. The results do not support a major sample selection bias that would complicate the interpretation of results in this first-episode psychosis study.